Integrated treatment utilizing both Chinese and Western medicine for refractory diabetic foot ulcers: a case report - Wang, Luyao; Sheng, Changting; Liu, Jiaxin; Chen, Rong; Yue, Rensong; Yang, Maoyi; Hu, Zhipeng (Frontiers in Endocrinology, 2025)
Diabetic foot ulcer (DFU) is a severe complication of diabetes associated with a high risk of amputation and long-term disability. We report the case of a 57-year-old man with a Wagner grade IV DFU whose condition continued to deteriorate despite two toe amputations. An integrative treatment strategy combining traditional Chinese medicine (TCM) and western medicine was subsequently employed and proved effective. The TCM regimen included oral decoctions and topical herbal applications, while the western medical approach encompassed targeted therapies including glycemic control, anti-infective therapy, circulatory enhancement, anticoagulation, neurotrophic support, and nutritional management. Over a 144-day course, the ulcer demonstrated near-complete closure at discharge, with full epithelialization and functional recovery confirmed at follow-up. HbA1c decreased from 13.5% to 7.0%, indicating improved metabolic control. This case illustrates that an integrative management strategy can effectively control infection, promote tissue regeneration, and restore limb function in advanced DFU.